Readings in the history of Christian theology ; vol. 2 - Placher, William Carl, 1948- (Phildelphia, PA Westminster, 1988)
Contents : v. 2 : From the reformation to the present. Includes bibliographical references and indexes.
Donated by The Australian College of Theology, 1996.
Keywords: Theology -- readings